2011
DOI: 10.1021/es201241g
|View full text |Cite
|
Sign up to set email alerts
|

Wood Biodegradation in Laboratory-Scale Landfills

Abstract: The objective of this research was to characterize the anaerobic biodegradability of major wood products in municipal waste by measuring methane yields, decay rates, the extent of carbohydrate decomposition, carbon storage, and leachate toxicity. Tests were conducted in triplicate 8 L reactors operated to obtain maximum yields. Measured methane yields for red oak, eucalyptus, spruce, radiata pine, plywood (PW), oriented strand board (OSB) from hardwood (HW) and softwood (SW), particleboard (PB) and medium-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 25 publications
5
62
0
Order By: Relevance
“…These forms of biomass address many of the concerns associated with the production of first-generation biofuels [3,4]. However, 10-35% of lignocellulosic biomass is composed of lignin [5][6][7], which is highly resistant to breakdown by the vast majority of microorganisms [8].…”
Section: Introductionmentioning
confidence: 99%
“…These forms of biomass address many of the concerns associated with the production of first-generation biofuels [3,4]. However, 10-35% of lignocellulosic biomass is composed of lignin [5][6][7], which is highly resistant to breakdown by the vast majority of microorganisms [8].…”
Section: Introductionmentioning
confidence: 99%
“…The door is transported to the landfill with a municipal waste collection truck. The behavior of specific wood products in landfill is not well documented (Wang et al, 2011;Ximenes et al, 2008). The Ecoinvent database does not include wood products in its landfill processes, only "wood untreated".…”
Section: End-of-lifementioning
confidence: 99%
“…Recent research has demonstrated that HWPs in landfill represent a long term C store, with minimal or no decomposition taking place. The mean loss of C (4.5%) determined from two key studies [6,8] is used in the estimates of long-term C storage for the HWPs in each of the case studies presented. The average loss of C reported in [6] was 9%, whereas [8] reported no C loss from blackbutt and radiata pine (Pinus radiata) exposed to optimised experimental anaerobic decay conditions.…”
Section: Carbon Storage In Hwpsmentioning
confidence: 99%
“…The mean loss of C (4.5%) determined from two key studies [6,8] is used in the estimates of long-term C storage for the HWPs in each of the case studies presented. The average loss of C reported in [6] was 9%, whereas [8] reported no C loss from blackbutt and radiata pine (Pinus radiata) exposed to optimised experimental anaerobic decay conditions. The proportion of C lost that was emitted as methane was assumed to be 50% [7], and it was assumed (conservatively) that no capture systems were in place to either flare the methane into CO 2 or to produce electricity.…”
Section: Carbon Storage In Hwpsmentioning
confidence: 99%
See 1 more Smart Citation